Corporate Ethical Values and Altruism: The Mediating Role of Career Satisfaction - Valentine, Sean; Godkin, Lynn; Fleischman, Gary M.; Kidwell, Roland E.; Page, Karen (2011)
This study explores the ability of career satisfaction to mediate the relationship between corporate ethical values and altruism. Using a sample of individuals employed in a four-campus, regional health science center, it was determined that individual career satisfaction fully mediated the positive relationship between perceptions of corporate ethical values and self-reported altruism. The findings imply that companies dedicating attention to positive corporate ethical values can enhance employee attitudes and altruistic behaviors, especially when individuals experience a high degree of career satisfaction.
Keywords: Citizenship; Altruism; career satisfaction; Corporate ethical values